Factors affecting students' information literacy self-efficacy. Issue 2 (17th June 2019) - Aharony, Noa; Gazit, Tali
Abstract : Purpose: The purpose of this paper is to explore how computer self-efficacy (CSE), perceived information overload (IO) and the digital native perspective predict students' information literacy (IL) self-efficacy. Design/methodology/approach: The research was conducted in Israel and comprised 117 students from the Information Science Department at Bar-Ilan University. Researchers used five questionnaires to gather personal details: a demographic questionnaire, the IL self-efficacy questionnaire, the CSE questionnaire, technology usage (TU) questionnaire and the perceived IO questionnaire. Findings: The findings confirm that these variables significantly predict students' IL self-efficacy. Originality/value: Instructors and librarians should be familiar with the issue of individual differences, as well with the issue of students' age. These factors may help them choose the most appropriate way when instructing IL skills to their students.